Service Failure and Recovery - Mishra, Amitabh (Indian Journal of Marketing, 2008)
Service provider's inability to perform services properly is known as service failure. After failure, dissatisfied customer may engage in complaint & evaluation process. If a customer finds that his complain will result in compensation and/or in any other forms of recovery, he may either complain to provider or to third party. The Customer's complaint provides the company with a chance to correct its mistake and satisfy its angry customer(s). Service provider's response to service failure decides customer's future purchase with the company. In the absence of positive response to the customers complain, probability of customer's switch over increases. It is found that mere compensation cannot retain customers for a long time; hence service provider should have a mechanism to minimize failure incidences.